مصادر الضغوط النفسية المهنية لدى عينة من الممرضين والممرضات "دراسة ميدانية في مستشفى الأسد الجامعي في محافظة اللاذقية" (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
هدفت هذه الدراسة إلى تعرُّف الضغوط النفسية المهنية التي يتعرَّض لها الممرضون والممرضات العاملين في مستشفى الأسد الجامعي وفقاً لمتغيرات (النوع، والحالة الاجتماعية)، وقد تكوَّنت عينة الدراسة من (120) ممرضاً وممرضة من مختلف الأقسام في المستشفى، واستخدمت الباحثة مقياساً للضغوط النفسية المهنيَّة من إعدادها، وقد خلصت الدراسة إلى النتائج التالية:- يعاني أفراد العينة من ممرضون وممرضات من ضغوط نفسيَّة بنسبة كبيرة (64.59)، إذ شكَّل البعد المادي المرتبة الأولى، يليه بُعد بيئة العمل، ثمَّ البُعد النفسي في المرتبة الأخيرة.- أظهرت الدراسة وجود فروق ذات دلالة إحصائية تعزى لمتغير النوع في الضغوط النفسية المهنية، وكانت هذه الفروق لصالح الإناث في البُعد النفسي، ولصالح الذكور في بُعد العلاقة مع الزملاء الأطباء، والبُعد المادي.- وجود فروق ذات دلالة إحصائية تعزى لمتغير الحالة الاجتماعية في الضغوط النفسية المهنية، ولقد كانت هذه الفروق في البُعد النفسي فقط ولصالح غير المتزوجين.This study aimed to identify the professional psychological pressures on a sample of nurses who are working in Al-assad University Hospital according to the variables (gender, marital status).The sample consistes of (120) nurses of various departments in the hospital. The researcher has done a questionair of the pressure professional psychological, the study concluded to the following results: -About (64.59) of the nurses have shown high levels of psychological stress. What comes first to the surface is the financial issues, then comes the work environment dimension and the psychological dimension.-The study showed that there were statistical significant differencesin favor of femalescocerningthe psychological dimension, and towardmales inthe dimension of the relationship with doctors as we the financialdimension.-The study showed that there were statistical significant differencesconcerning professional psychological pressures. These differences were related to the psychological dimension and in favor of unmarried people only.